Wildfire Smoke Demonstrates Significant and Predictable Black Carbon Light Absorption Enhancements - James E. Lee; Kyle Gorkowski; Aaron G. Meyer; Katherine B. Benedict; Allison C. Aiken; Manvendra K. Dubey (Geophysical Research Letters)
Abstract Black carbon (BC) is estimated to have the second largest anthropogenic radiative forcing in earth‐systems models (ESMs), but there is significant uncertainty in its impact due to complex mixing with organics. Laboratory‐generated particles show that co‐mixed non‐absorbing material enhances absorption by BC by a factor of 2–3.5 as predicted by optical models. However, weak or no enhancements are often reported for field studies. The cause of lower‐than‐expected absorption is not well understood and implies a lower radiative impact of BC compared to how many ESMs currently treat aerosols. By analyzing BC aerosol particle‐by‐particle we reconcile observed and expected absorption for ambient smoke plumes varying in geographic origin, fuel types, burn conditions, atmospheric age and transport. Although particle‐by‐particle tracking is computationally prohibitive for sophisticated ESMs we show that realistic BC absorption is reliably estimated by bulk properties of the plume providing a suitable parameterization to constrain black carbon radiative forcing.